How the strain effects decreases the band gap energy in the CsPbX3 perovskite compounds?. (3rd May 2020) - Zitouni, H.; Tahiri, N.; El Bounagui, O.; Ez-Zahraouy, H.
ABSTRACT: The perovskite cesium lead halides have been proposed as promising materials for photovoltaic devices because of their visible light absorption and direct band gap semiconductors. The structural, electronic and optical properties of the bulk CsPbX3 (X = Br, Cl and I) are studied, using density functional theory. In order to use these compounds in photovoltaic applications, the only inconvenient of these materials is that they have a slightly high gap energy value such as: 2.57, 2.16 and 1.88 eV for CsPbCl3, CsPbBr3 and CsPbI3 compounds, respectively. It is known that the efficiency of the solar cells varied with the band gap of the materials used. Moreover, by applying 3% of strain on the perovskite CsPbX3, we have reducing the gap energy value of these materials. The present compounds are one of the promising candidates for photovoltaic applications.